Spine radiosurgery for spinal cord compression: the radiation oncologist’s perspective - Regine, William F. (J Radiosurg SBRT, 2011)
Metastatic spinal cord compression (MSCC) is a common problem afflicting cancer patients. It affects 5-14% of all patients with cancer, and more than 20,000 cases are diagnosed annually in the United States (1-3). Once diagnosed, it is considered to be a medical emergency, and immediate intervention is required with high-dose corticosteroids and radiotherapy (RT), with or without decompressive surgery. Without therapy, MSCC is a source of significant morbidity and mortality, causing pain, paralysis, incontinence, and an overall decline in quality of life. Even with aggressive therapy, results can often be unsatisfactory. Although most patients will die of their underlying cancer within the first year of the diagnosis of MSCC, up to one-third will survive beyond one year (4-5). Therefore, optimal therapy is required to maintain quality of life.